A survey on sports activity involvement, menstrual history and eating disorders in Malaysian elite female athletes / Afiqah Khairunnisa Yunan ... [et al.] - Yunan, Afiqah Khairunnisa; Ooi, Foong Kiew; Ahmad, Nur Syamsina; Abdul Raof, Nur Dalila Adilah; Yeo, Wee Kian; Ong, Kong Swee (Universiti Teknologi MARA, 2023)
This study investigated sports activity involvement, menstrual history, and prevalence of eating disorders among Malaysian elite female athletes. A total of 50 female national and state level athletes with a mean age of 21.16 ± 2.31 years old participated in this study. They were 6 gymnasts, 17 swimmers, 5 cyclists, 7 long distance runners, and 15 silat athletes. The participants were required to answer the sports activity involvement questionnaire, menstrual history questionnaire, and Eating Disorder Examination Questionnaire (EDE-Q). The present study found that 44 (88%) of the total participants had regular menstruation, while 6 (12%) participants had irregular menstruation. The global score of EDE-Q subscales was 1.71 (60 to 65 percentile rank) in all the participants. Comparisons of measured variables between participants with regular menstruation and irregular menstruation showed that age in years at the beginning of training was younger in participants with irregular menstruation (9.83 ± 4.07) than participants with regular menstruation (11.84 ± 3.52). The global score of EDE-Q subscales was higher in participants with irregular menstruation (2.32; 75 to 80 percentile rank) than participants with regular menstruation (1.63; 60 to 65 percentile rank). In conclusion, the results of the present study show that participants with irregular menstruation seem to have higher global score of EDE-Q subscales, i.e., restrain, eating concern, shape concern, and weight concern. Irregular menstruation may be related to the young starting age of the athletes involved in training and the long total training period in years.